Technology transfer: the case of the Centro de Desenvolvimento da Tecnologia Nuclear (Nuclear Technology Development Center) - Xênia Aparecida Chaves Santos; Régia Ruth Ramirez Guimarães; Gustavo José Pereira; Sérgio Almeida Cunha Filgueiras (Brazilian Journal of Radiation Sciences, 2021)
The technology transfer is part of the innovation process and has the role of contributing to local and national economic development. As a form of insertion in the National Innovation System, this study was made with the goal of presenting how the technology transfer is being made in the CDTN. Based on a survey carried out by the NIT-CDTN of the technologies developed in the institution, a portfolio of key information on technologies developed was made with the main objective of evaluating those technologies, using the degree of maturity and economic interest to classify them. CDTN technologies have a reasonable potential for generating value, yet they need technological maturity to achieve the transfer to the market. The study carried out by NIT-CDTN shows that CDTN already has a good set of tools to promote high quality technological innovation. The Technology Readiness Level (TRL) was used to evaluate the maturity level of technologies with higher transfer potential. To ensure the success of the transfer, it is necessary to consolidate the methodology to include key aspects such as valuation, market research and adaptation of existing methodologies according to the need of the institution and the market. To conclude, it is perceived that the ideal would be to invest in the most promising technologies to have a breakthrough for the pilot scale.